Evaluation of Drip Test Sampling Plan in Carcasses of Frozen Broilers - Santos, Daisy Viviane Silva; Barros , Ludmilla Santana Soares e; Mascarenhas, Maria Tereza Leal Vargas; Lima, Katia Cerqueira (International Journal of Poultry Science, 2013)
Current assay evaluated the efficacy of the Drip Test Sampling Plan according to Brazilian legislation. The experiment was carried out in a poultry slaughterhouse under the official state supervision office, located in Recôncavo da Bahia, Brazil, between September 2011 and February 2012. Sample was prepared and its batch number was identified by the number of the truck to be unloaded on that day. One hundred and five samples were collected, with 10 chickens in each batch, for Internal Control Method. On the day after freezing, the Drip Test was conducted in 90 batches with 12 chickens each, totalizing 1.080 frozen chickens, according to the batch that had been analyzed the day before. Variables that involved the process were controlled by the industry’s quality sector. The Drip Test was carried out according to the official methodology laid down by 210/1998 Ordinance of the Ministry of Agriculture, Livestock and Food Supply and compared to double the sampling plan. Results showed that the sample standard with an average of 6 carcasses was efficient when compared to the 12-carcass average.